A start codon mutation of the TSPAN12 gene in Chinese families causes clinical heterogeneous familial exudative vitreoretinopathy. Issue 10 (26th August 2019) - Li, Wei; Wang, Ziwei; Sun, Yan; Wang, Zhuoshi; Bai, Jinyue; Xing, Bo; Sun, Xiao; Wang, Lusheng; Li, Jiankang; He, Wei
Abstract: Background: Familial exudative vitreoretinopathy (FEVR) is a severe clinically and genetically heterogeneous retinal disorder characterized with failure of vascular development of the peripheral retina. The symptoms of FEVR vary widely among patients in the same family, and even between the two eyes of a given patient. The purpose of this study was to investigate the molecular mechanisms by which the start codon mutation of the TSPAN12 causes difference in clinical manifestations between individuals in the same family. Methods: Next‐generation sequencing (NGS)‐based target capture sequencing was performed in proband with a diagnosis of FEVR and their normal visual acuity family members. Cosegregation analysis of the candidate causative variant was performed in additional family members by using Sanger sequencing. Complete fundus examination, fundus fluorescein angiography (FFA), and family history collection were performed in all family members. Potential candidate causative variants were verified with reference to guidelines and standards from the American College of Medical Genetics and Genomics. Results: We identified a novel heterozygous missense mutation (c.1A>G, p.M1V) localized in the start codon of the TSPAN12 and was detected as a potentially disease‐causing variant for the proband. Retrospective analysis of clinical data, fundus examination, and FFA showed that the mutant carrier presented peripheral retinal vascular anomalies in early stages, and visual acuity did not show significant effects. However, the proband who carried this mutation and his cousin showed typical high‐stage FEVR fundus changes coupled with a sharp decline in vision. Conclusions: We report a novel start codon mutation (c.1A>G, p.M1V) in the TSPAN12 that causes clinically heterogeneous manifestations. Our results expand the mutation spectrums of TSPAN12, and will be valuable for disease diagnosis, prognosis, genetic counseling, and enriching our understanding of the role of the tetraspanin‐12 protein in the pathogenesis of FEVR. Abstract : We report that a start codon mutation of the TSPAN12 in Chinese families causes clinical heterogeneous familial exudative vitreoretinopathy, and that mutant carriers with lesions occurring in the peripheral retinal vessels may present normal visual characteristics, whereas mutant carriers with lesions occurring in the vascular region may present a severe clinical phenotype with rapid progression.